Pengaruh Religiusitas, Integritas, dan Penegakan Peraturan Terhadap Fraud pada Pengelolaan Keuangan Desa - Made Feri Cahyadi; Edy Sujana (Jurnal Ilmiah Akuntansi dan Humanika, 2020)
The purpose of this study was to find out the effect of religiosity, integrity, and enforcement of regulations toward fraud in village financial management in Buleleng Regency. This study used quantitative approach which was using primary data sources that was obtained through questionnaires and measured with a Likert scale. The functionary village consisting of the Headman, Secretary, and the Head of Finance with the total population of 387 functionary village in Buleleng Regency were chosen as the population of this study. The sampling was the probability sampling method that was proportional random sampling technique with 168 respondents. The obtained data were processed using multiple linear regression analysis method with the support of SPSS 24.0 for Windows. After being tested, it was found that the fraud in village financial management was affected by the religiosity variable (X1), the integrity variable (X2), and the enforcement regulation variable (X3).